2005
DOI: 10.1007/s00038-004-3103-1
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination of hospital staff in Germany: a five-year survey on vaccination coverage and policies: identified deficits in influenza immunisation campaigns for hospital employees

Abstract: Considerable progress has been made to involve more hospitals and to increase coverage for vaccination of hospital employees. Nevertheless, coverage levels remain unacceptably low. Recommendations are ignored extensively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
(9 reference statements)
0
6
2
1
Order By: Relevance
“…However, working in the medical field in Germany did not markedly encourage vaccination, with the odds in this group never even doubling those in the non-target group. Earlier publications on influenza coverage rates [4,9,[26][27][28][29] already noted a low coverage in health-care workers in Germany, ranging from 8% [27] to 26% [26]. By comparison, we found a vaccination coverage range between 22% and 26% in the surveys from 2001/02 to 2006/07, while the non-target group remained < 18%.…”
Section: Discussioncontrasting
confidence: 42%
“…However, working in the medical field in Germany did not markedly encourage vaccination, with the odds in this group never even doubling those in the non-target group. Earlier publications on influenza coverage rates [4,9,[26][27][28][29] already noted a low coverage in health-care workers in Germany, ranging from 8% [27] to 26% [26]. By comparison, we found a vaccination coverage range between 22% and 26% in the surveys from 2001/02 to 2006/07, while the non-target group remained < 18%.…”
Section: Discussioncontrasting
confidence: 42%
“…This worked, as coverage increased from 10% (1995)(1996) to 26-37% (1996-1997). More recently, a significant increase of vaccination rates among the staff of 25 German hospitals over 5 years was achieved using posters in the wards and common areas, combined with active support from hospital management [50].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies [30,31], influenza immunization rates of HCWs were similar to the numbers reported in the study by Abramson and Levi. Earlier publications on influenza coverage rates [15][16][17][18][19] already noted a low coverage in health care workers in Germany, ranging from 8% [32] to 26% [31].…”
Section: Discussionmentioning
confidence: 99%